Enabling Industry 4.0 through Advances in Mechatronics - Ahmad Shahrizan, Abdul Ghani; Ismail Mohd., Khairuddin; Muhammad Amirul, Abdullah; Ahmad Fakhri, Ab. Nasir; Jessnor Arif, Mat Jizat; Mohd. Azraai, Mohd. Razman; Muhammad Aizzat, Zakaria; Wan Hasbullah, Mat Isa; Anwar P. P., Abdul Majeed (Springer Singapore, 2022)
This book presents part of the iM3F 2021 proceedings from the mechatronics track. It highlights key challenges and recent trends in mechatronics engineering and technology that are non-trivial in the age of Industry 4.0. It discusses traditional as well as modern solutions that are employed in the multitude spectra of mechatronics based applications. The readers are expected to gain an insightful view on the current trends, issues, mitigating factors as well as solutions from this book.